Peran Media Sosial Dalam Meningkatkan Atau Menghambat Produktivitas Mahasiswa - Bu'ulolo, Welman; Hulu, Marcel Kurniawati (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Social media has become an integral part of students' lives, offering various benefits yet also challenges that affect their productivity. This study aims to explore the role of social media in enhancing or hindering student productivity by examining positive aspects such as access to information, collaboration, and social networking, as well as negative impacts like distraction, decreased study quality, and a tendency to procrastinate. The analysis results indicate that social media can boost productivity when used for academic purposes, group discussions, and sharing educational information. However, social media can also become a hindrance when overused, leading to dependency or being utilized solely for entertainment. Factors such as usage duration, purpose, and time management play an important role in determining its positive or negative impacts. With a better understanding of the role of social media, students are expected to use it more wisely to support their academic productivity.